Neutralization Sensitivity and Evolution of Virus in a Chronic HIV-1 Clade B Infected Patient with Neutralizing Activity against Membrane-Proximal External Region - Wenqi Tang; Zhenzhen Yuan; Zheng Wang; Li Ren; Dan Li; Shuhui Wang; Yanling Hao; Jing Li; Xiuli Shen; Yuhua Ruan; Yiming Shao; Ying Liu (Pathogens, 2023)
The membrane-proximal external region (MPER) is a promising HIV-1 vaccine target owing to its linear neutralizing epitopes and highly conserved amino acids. Here, we explored the neutralization sensitivity and investigated the MPER sequences in a chronic HIV-1 infected patient with neutralizing activity against the MPER. Using single-genome amplification (SGA), 50 full-length HIV-1 envelope glycoprotein (env) genes were isolated from the patient’s plasma at two time points (2006 and 2009). The neutralization sensitivity of 14 Env-pseudoviruses to autologous plasma and monoclonal antibodies (mAbs) was evaluated. Env gene sequencing revealed that the diversity of Env increased over time and four mutation positions (659D, 662K, 671S, and 677N/R) were identified in the MPER. The K677R mutation increased the IC50 values of pseudoviruses approximately twofold for 4E10 and 2F5, and E659D increased the IC50 up to ninefold for 4E10 and fourfold for 2F5. These two mutations also decreased the contact between gp41 and mAbs. Almost all mutant pseudoviruses were resistant to autologous plasma at both the earlier and concurrent time points. Mutations 659D and 677R in the MPER decreased the neutralization sensitivity of Env-pseudoviruses, providing a detailed understanding of MPER evolution which might facilitate advances in the design of HIV-1 vaccines.